Think Before Getting Addicted to Smartphones ! - Dwivedi, Sunita; Altekar, Shrirang; Phutela, Nidhi (Indian Journal of Marketing, 2019)
In the present times, individually, everyone, knowingly or unknowingly, has acquired a habit of integrating cell phone usage with their day to day lives. Perpetually, this has developed an addiction towards smartphones. Philanthropists and academicians are inclined towards knowing whether this habit is really an act of updating to make oneself more tech - savvy or whether such a habit makes any value addition to our lives. Henceforth, it was quite essential to investigate the effect of smart cellphone usage on behavioral issues of people and to determine what kind of changes are brought in an individual’s psyche and psychology due to excessive usage of smartphones. Previous studies focused more on understanding the different aspects of smartphone usage but rarely tried to determine what happens if anyone uses smartphones in excess. In our research, we established the triangulate relationship between smartphone usage, technostress, and conflict behavior. We determined whether smartphone usage leads to technostress impacting an individual’s conflict behavior or whether technostress mediates this relationship. The study was conducted among respondents in the age bracket of 17 - 66 years representing various social strata. This research was quantitative in nature and used SEM to validate the relationship between smartphone addiction, technostress, and conflict behavior. The results of the research concluded that there was a significant impact of smartphone addiction on conflict behavior. This research has strong implications for HR managers to design various OD interventions for employees; philanthropists/counselors to start movements for youngsters and older people to harmonize their intra-personal issues.